Assessing the economic performance of cocoa agroforestry in Ghana - Akoto-Adjepong, Vera (2016)
A thesis submitted to the School of Graduate Studies, Kwame Nkrumah University of Science and Technology, Ghana in partial fulfillment of the requirements for the award of a Master of Philosophy Degree in Agricultural Economics